Investigation of possible aqueous phase formation during vaporization of sevoflurane - Shane Varughese; Vikram G Kalthod; James P Petzel; Hans Peter Bacher; Arthur W Wallace (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Ultane®(sevoflurane; AbbVie Inc., North Chicago, IL, USA) has a dissolved water content of approximately 0.035% weight/weight (w/w). A previous report described formation of an aqueous layer in 4 of 13 sevoflurane vaporizers used in operating rooms. We investigated the conditions under which an aqueous layer could develop during vaporization of sevoflurane-water mixtures. Material and Methods: A temperature-controlled glass reactor was used to simulate a vaporizer. In four experiments, the vaporization of different sevoflurane-water mixtures was monitored over approximately 3-4 days. Samples were removed at regular intervals for analysis of water content. For confirmation, one experiment was replicated in a Tec 7 vaporizer. Results: Saturation of sevoflurane with water occurred at 0.11%-0.13% w/w at an ambient temperature; at greater water concentrations a separate aqueous phase was initially present. The sevoflurane-water azeotrope contained approximately 1.2% w/w water at 25°C. When the initial water content was <1.2% w/w (0.11%-1.03% w/w), vaporization resulted in a single phase of drier sevoflurane (final water concentration 0.02%-0.08% w/w). When the starting water concentration exceeded the azeotropic concentration (5.0% w/w), vaporization increased the water content, reaching 13% w/w at 71 h. Results under the low initial water condition were similar in the Tec 7 vaporizer. Conclusions: An increase in water concentration following vaporization of sevoflurane can only occur when the starting water content is higher than the azeotropic concentration and therefore cannot originate from the dissolved water present in the marketed product because the water concentration in Ultane®is 34 times lower than the azeotropic concentration.